The Woman’s Silent Voice toward Patriarchy’s Handcuff Reflected in AtiqRahimi’sThe Patience Stone - RIZKI SURYA ADI P (LITERA KULTURA : Journal of Literary and Cultural Studies, 2013)
Abstrak Patriarkiadalah salah satumasalahbesar bagisetiapwanita di dunia, masalah iniakhirnyadiwakilidengankarya sastra, dansalah satunya adalahAtiqRahimiBatuKesabaran.Terdapat Perempuan, sebagai karakter utamadiceritakandengan semuakesedihan, menikahdengan dipaksa, menikahdengan foto, sampai diaharus membuathamil dengantanpajalan dandia memilikibayi daripria laindia tidak pernahtahu. Berdasarkanfakta-fakta, ini memberikan dua pertanyaanutama sebagairespondarimasalah, adalah(1) GambaranbelenggupatriarkimelaluisuaradiamPerempuandiAtiqRahimiBatuKesabaran?(2) DampaksuaradiamPerempuandiAtiqRahimi, BatuKesabaran?Untuk mengatasi hal itudengan analisis, membutuhkanmetode yangmembaca, mengumpulkan data, dan interpretasi, teknik yang digunakanadalahinterpretasi, dan pendekatanmimesis. Sebagaihasil dariini, itu akanmenemukan sesuatu, suaradiamPerempuan, dan initerjadidi Afghanistan, oleh karena itu,dapat dikatakanbahwa sistempatriarkibisa mengambilhak-hak perempuan, dan apahal-hal yangdapat memberikanPerempuanadalahsuaradiam,suarayang dapat menjadigerakan feminisuntuk setiapsimpatiuntuknya. Ini mewakili, untukberkatadalam bisikanyang sangathalus yangmasih adaketimpanganyang disebabkan olehpatriarki, danWanitatidak dapatberbuat apa-apa. Kata Kunci: Patriarki, perempuan, suaradiam, danfeminisme. Abstract Patriarchy is one of the great problem for every women in the world, this problem finally is represented to a literary work, and one of it is AtiqRahimi’sThe Patience Stone. There, the Woman, as the main character is told with all sorrow, marrying by being forced, marrying with a photo, until she has to make pregnant with regardless the way and she has baby from another guy she never knows. Based on the facts, it delivers two main questions as the response of problems, they are (1) Depiction of patriarchy’s handcuffthrough the Woman’s Silent Voicein AtiqRahimi’sThe Patience Stone? (2) The impact ofthe Woman’s Silent Voice in AtiqRahimi’sThe Patience Stone? To solve it by analysis, it requires a method that is reading, collecting data, and interpretation, the used technique is interpretation, and the approach is mimesis. As the result of this, it will find something, the silent voice of the Woman, and this is happen in Afghanistan, therefore, it can be said that patriarchy system can grab the rights of women, and what things that the Woman can deliver is the silent voice, the voice that can be a feminist movement for every sympathy to it. It represents, it says in very smooth whispers that there are still inequality caused by patriarchy, and the Woman cannot do anything. Keywords: Patriarchy, women, silent voice, and feminism. INTRODUCTION Human lives in the world are like corrosion on the ply of metal in the process of abrasion. What the core of this analogy is the way human wear their brain shell to think and find the solution of every problem they face to. Human are divided in to two genders normally, they are men and women. Men, a creature whose penis sticks strongly with dignity and power to dig every hole in front of it. Women, a creature whose vagina decorates beautifully with softness and warmness for everything that prepares for digging it. Based on the differences of the two, the conflicts arise. It starts when women begin realizing that what they think is their right, is grabbed by the creature, called men. In addition, this thought probably can be supposed as the basic thought of feminism movement. Before going further to the meant feminism, it is important to see what feminism fights to, and it is patriarchy system. Patriarchy system is a system that has been rooted in society generally. Erich From asserts that Patriarchy system is where men is fated to dictate/control women, and it rules to all part in the world. (Fromm, 2002: 177). To add it, to make the establishment of this system of men, chronologically there are some experts that give distance between men and women where men are supposed to be the better one. Classically, women are inequality creature, and it is added by Aristotle who views women as an imperfectness of nature (Beauvoir, 2003:ix). Francis Bacon comments that the more negative assertion that women are the jail of men because women give bad effect or influence to men (Arivia, 2002:40). Kant even says that women does not have any ability to use their cognitive ability therefore women should not be allowed to deliver what they think (Arivia, 2002:40). While, St. Thomas supposes women as “imperfect men”, women are creature who are created not deliberately, and it is proven by the symbolic story where Eve is portrayed by Bossuet as a creature who is made of the “Adam’s Rib” (Beauvoir, 2003:xi). According to Cixous, the term of men and women pinpoints to the difference of the two where the first term must posit the higher or better meaning, and it is placed by men. Therefore, men are self and women are the Liyan. Women live in men’s world, therefore women are considered as the Liyan for men. (Tong, 2009: 292). Based on those facts, society finally construct a system where men dominate the whole contents of social life. J. Douglas (1976: 34) adds that many feminists use the term patriarchy as a generic term for male privilege, supremacy, and domination, referring to their current as well as past forms. The attraction of this usage is readily apparent: first, its rhetorical punch and strongly pejorative connotations; second, its reminder of the tenacity and continuity of male domination. Despite earth-shaking social changes, not the least of which are the women's Movements of the nineteenth and twentieth century, male power remains. Therefore, what the things that can be inferred into these facts are the problems between men and women. Feminism moves to throw everything that involves in men’s domination because they dictate women, women seem to live in a coop. It means that what women fight is the system of men. In general, feminism is the theory of women’s liberation since the intrinsic in all its approaches is the belief that women suffer injustice because of women’s sex (Humm, 1989: 74). From the inequality that exists between both gender, women want to search equality in the society, they start to speak up their voices in the publicarena. Women themselves must articulate who they are and what role they play in the society. Most importantly, they must reject the patriarchal assumption that women are inferior to men. This started the feminist movement. It was started by the reality that male-female relations is a form of power structure in which men dominate women (Thebaud, 1994: 290). From this starting point the feminist believe that existing inequalities between dominant and marginalized groups can and should be removed. In the practive the feminist scholars attempt to examine beliefs and practices from the viewpoint of the “other”, in this case women, treating them as subjects, not merely objects. Based on those views, it can be said that feminism simply is a thought that focuses on the equality between men and women, especially to talk about the rights of women. Therefore, what things that can be put into the main topic of this, is the all things relates to the inequality between men and women where men are supposed to be the superiority ones. Feminism itself is part of cultural studies in literature, which arises since women feel discredited and being treated unequal to men as human. Yet, what is not acceptable is the differentiation in position, that men are superior to women. That awareness prompts women to rise up and fight for their rights. Feminism deals with freedom, appreciation, and fair treatment for women. It is not women’s disability to sit equal with men, but the systems in their social life discourage women to gain self-assertion to actualize themselves as well as men. Meanwhile, women want to grow as human beings who have equal role and opportunity in their own life and society. In the West and East alike, feminists were up against home-grown patriarchalist opponents who used sundry means to denigrate feminism and its supporters. In the West, detractors portrayed feminists as man-haters. In the East, enemies branded feminists as agents of cultural subversion and, ironically in so doing ‘colluded’ with westerners in declaring feminism western. (Kynsilehto, 2008: 26). Therefore, what can be integrated from this Islam feminism understanding is the way Islam see the equality between men and women, from the agents of truth about the equality between men and women, not creating women to hate men just to beg an equality as what west feminism says to. It is clear to see that this problem finally inspires some authors to write it down in beautiful work, and one of it is AtiqRahimi with his novel entitled The Patience Stone. The main thing that is hidden in AtiqRahimi’sThe Patience Stone is the way feminism is shown up. This novel, especially the main character, the woman, erodes the feeling of the readers to give sympathy and tears on what has happened to the woman. The woman cannot fight to the system of men he faces on, but she just can deliver it through a telling to her comate husband, which is not changing anything to her fair life. Specifically, in Atiq Rahimi’s The Patience Stone, there is told a woman sits in front of his comate husband. She tells everything she never confesses before because of some reasons. She is the wife of a soldier who is lying unconscious with a bullet in his neck, and she calls her husband with The Patience Stone or “Sang-e Saboor,” it is a mythical stone accords to Persian folklore that absorbs the pain of those who confide in it, until it eventually explodes. When the novel opens, the man has been comatose for over two weeks, and shows no signs of recovery. Frustration and despair on the woman’s part gradually turns to angry rebellion and, uncertain whether or not he can hear her words, she becomes ever more talkative and outgoing as she gathers over their ten-year marriage. The thing that is important to know is that the couple didn’t meet before their wedding, nor even during it, since he was away fighting. Instead a ceremony was performed between the teen bride (the Woman) and a photograph, after which she spent three years as a married virgin. She is not allowed to be out of house of seeing friends and family. When the Husband returns, she discovers that she is married to a violent, because the Husband brutally detaches sex at the first sex time. It can be seen that the woman as main character reflects “handcuff” of women life against patriarchy in the social life of the novel. The Women uses her inability to comprehend and talk back to tell him things that she will not dare to say otherwise. With his disability she has been left to feed herself, her two children and continue buying medicine to keep her husband alive. The only job available for an Afghan woman in her desperate situation it seems is prostitution. It is an interested topic to explore because AtiqRahimi’sThe Patience Stone is part of a Persian myth about a stone that has this phenomenal strength to listen to stories of suffering and sorrow. What sorrow that is delivered is from the heart voice of a woman that lives in the unfair world. The unfair world is caused by the inequality. Thus, to respond it, the readers must have attention to give sympathy to the woman indirectly, and to call this feeling, it is not too naïve when it said as the feminist movement that calls everyone in talking the equality women should have. To classify it, this thought belongs to first wave, where women have voice to utter although it is not a fight directly. Then, the voice that is not changing anything significantly to what the Woman faces, is the silent voice. Silent voice is the voice that is not heard, listened, and sensed. However, this voice exists, and the existence gnaws sympathy to see how unequal the social system the Woman faces, the sympathy that dribbles to feminism thought indirectly to get the equal rights. Based on the reasons above, this thesis then conveys analysis on the life and some aspect of main characters thorough feminism approach accords to patriarchy concepts and understanding in AtiqRahimi’sThe Patience Stone. Finally, the planned title can be written as The Woman’s Silent Voice toward Patriarchy’s Handcuff Reflected in AtiqRahimi’sThe Patience. For more additional support that this thesis uses credible object, it is important to see that AtiqRahimi’sThe Patience Stone is the winner of Prix Goncourt Prize in 2008. Therefore, this thesis hopefully can be a great product and be great donation of literary critics and analysis. Indeed, the decision to select AtiqRahimi’sThe Patience Stone rather than the other works of him is caused by the main topic of the work. AtiqRahimi’s The Patience Stone delivers more complex problem between men and women, that finally grabs the problem of Patriarchy and Feminism, while the feminism that is used is based on the glasses of Islam because the setting is in Afghan. In AtiqRahimi’sEarth and Ashes is told about the patriotic father that struggle with his blind son during the Russia invasion in Afghanistan, while in AtiqRahimi’sA Thousands Room of Dream and Fear delivers a student who exiles form his life because he is chased, he loves someone saves him. Based on the two reference, AtiqRahimi’sThe Patience Stone becomes the best one to analyze accords to men and women problem culturally. RESEARCH METHOD This study is taking one of the Atiq Rahimi’s stories entitled The Patience Stone as the primary source. In case of analyzing this story, library research is used in order to find some theories, which are relevant to the topic. Finally, Mimesis approach will be used in analyzing this story because the topic that will be discussed about the main character’s silent voice as a woman against patriarchy in her social life as the universal truth. In collecting data, this research focuses on analysis and citations. The first step is reading novel. In this step, novel becomes the object of the research. The novel is entitled The Patience Stone, written by Atiq Rahimi. This is to reach the understanding all contents completely with all possibilities both intrinsically and extrinsically. The second is inventorying data. This step is collecting data through noting the quotations related to the statement of the problems and objectives of the study, it is including in words, sentences, and discourse that can represent patriarchy and feminism in Atiq Rahimi’s The Patience Stone. The third is classification data. This step to classify the data based on the statement of the problems including the portrayal patriarchy and the way the Woman posits herself against it. The fourth is tabling the data. It is to simplify reading the data and classify data that is used in the analysis for the readers. Those collected data are continuosly intrepreted to react the statement of the problems. The handling of a technique is a duty to do, it is to keep the analysis not jumping out of the limitation in order to solve the statement of the problems. Furthermore, it is significant to be on familiar terms with the data that it is from the novel entitled The Patience Stone, written in 136 pages plus 4 pages of brief introduction by KhaledHossaeni. It is written by AtiqRahimi with original title of SynguéSabour. Pierre de patience, published with ISBN: 9780701184102, and by Chatto&Windus. It is addressed at Random House, 20 Vauxhall Bridge Road, in London at 7wiv 25a. The book design is created Chatto and Windus group and translated by Polly McLean. On the dark cover, there is laid a stamp of Goncourt Winner 2008. CULTURAL APPROACH The term culture is a description of a particular way of life, which expresses certain meanings and values not only in art and learning but also in institutions and ordinary behavior (Frow, 1996: 8). Frow also states that culture is the way of life and is the meanings and values in that way of life. Therefore, basically a cultural approach is a way to think about a literary text based on the ideas or customs of certain society in which the text is made. According to Stanley Fish, J. Hillis, and Michael Foucault, language helps create what we call objective reality, thus reality is a social construct since it is created from language which is a product of customs produced by certain society. (Bressler, 1999: 264) Each society or culture contains in itself a dominant cultural group which determines that culture’s ideology, its dominant values it sense of right and wrong, and its sense of personal self worth. (Bressler, 1999: 264) Culrural approach is divided into some theories. Those are: Marxism, post colonialism, new historicism, and feminism (Bressler, 1999: 178). As stated above, cultural approach investigates the domination and the dominated groups. Therefore, this approach will be used to analyze Atiq Rahimi’s The Patience Stone and since the dominated group in this novel is women, the theory of feminism will be used for further analysis. Before going deeper to the feminism, it is important to see that feminism that will be used is the feminism from the glasses of Islam. In the West and East alike, feminists were up against home-grown patriarchalist opponents who used sundry means to denigrate feminism and its supporters. In the West, detractors portrayed feminists as man-haters. In the East, enemies branded feminists as agents of cultural subversion and, ironically in so doing ‘colluded’ with westerners in declaring feminism western. (Kynsilehto, 2008: 26). Therefore, what can be integrated from this Islam feminism understanding is the way Islam see the equality between men and women, from the agents of truth about the equality between men and women, not creating women to hate men just to beg an equality as what west feminism says to. This thought is also influence to the way of the culture move by times, Eastern as universal truth sees, is culturally have features of moral, politeness, differences, and those all shape a unity of eastern culture that is very cultural. While, in Western, thought, rationality, and will or dreams becomes the subjects that move them to be better, and it shapes their mind and finally becomes the culture of west, therefore, the freedom of women seems to be radical rather that to grab the equality. PATRIARCHY Patriarchy system is a system that has been rooted in society generally. Erich From asserts that Patriarchy system is where men is fated to dictate/control women, and it rules to all part in the world. (Fromm, 2002: 177). Engels gives different perspective that patriarchy system is begun when human have already understood about privacy owning, and it marks the birth of system of class. (Budiman, 1981: 21). What Engels means, must reflect to the birth of system of class of men and women. To add it, to make the establishment of this system of men, chronologically there are some experts that give distance between men and women where men are supposed to be the better one.Classically, women are inequality creature, and it is added by Aristotle who views women as an imperfectness of nature (Beauvoir, 2003:ix). Francis Bacon comments that the more negative assertion that women are the jail of men because women give bad effect or influence to men (Arivia, 2002:40). Kant even says that women does not have any ability to use their cognitive ability therefore women should not be allowed to deliver what they think (Arivia, 2002:40). While, St. Thomas supposes women as “imperfect men”, women are creature who are created not deliberately, and it is proven by the symbolic story where Eve is portrayed by Bossuet as a creature who is made of the “Adam’s Rib” (Beauvoir, 2003:xi). According to Cixous, the term of men and women pinpoints to the difference of the two where the first term must posit the higher or better meaning, and it is placed by men. Therefore, men are self and women are the Liyan. Women live in men’s world, therefore women are considered as the Liyan for men. (Tong, 2009:292). Based on those facts, society finally construct a system where men dominate the whole contents of social life. J. Douglas (1976: 34) adds that many feminists use the term patriarchy as a generic term for male privilege, supremacy, and domination, referring to their current as well as past forms. The attraction of this usage is readily apparent: first, its rhetorical punch and strongly pejorative connotations; second, its reminder of the tenacity and continuity of male domination. Despite earth-shaking social changes, not the least of which are the women's Movements of the nineteenth and twentieth century, male power remains. These all continuously give a perspective that women are really controlled, handled, and dictated by men particularly in society. The representation of society can be found in family. Family is the crucial institution in society (Millet, 1972: 33) because it can represent to what happens in the society. In a family the women mostly being the victim of oppressed by their husband or brother. Furthermore, feminist knowledge develops and becomes more sophisticated throughout the 1970s; the family comes to be an important object of analysis. In many cases, it is the crucial site of women s oppression, the space where, unheeded by the world outside, women are at the mercy of fathers or husbands; where the law of patriarchy holds its most primitive form (Pilcher&Whelehan, 2004: 44). Engels as quoted by Millet explains that the ideal type of the patriarchal family and the ancestor is the Roman family, whence come both the term and the legal forms and precedents in the west. Engels informed the word familiaas follow: signify the composite ideal of sentimentality and domestic strife in the present day philistine mind. Among the Romans it did not even apply in the beginning to the leading couple and its children, but to the slave alone. Famulus means domestic slave, and familia is the aggregate number of slaves belonging to one man the expression [familia] was invented by the Romans in order to designate a new social organism the head of which had a wife, children and a number of slaves under his paternal authority and according to Roman law, the right of life and death over all of them(Millet, 1972: 123—124). In family, Gough as quoted by Jo, mentions that men and women cooperate through a division of labor based on gender. Child care, household tasks and crafts closely connect with the household, tend to be done by women; war, hunting, and government by men. Besides that, men in general have higher status and authority over the women of their families, although older women may have influence, even some authority, over junior men (Jo, 1984: 84). Therefore, what things can be inferred to those all understandings, are the problem that is faced by women in the society, the society is like the jail of women and it is sourced by thoughts where place men in a good position to control women. This is also what things reflected on AtiqRahimi’sThe Patience Stone that finally makes the main character, the woman, whispers something as the silent voice in the middle of patriarchy system. This reaction potentially can be said as the thing to get attention and sympathy about what happens to women in Afghanistan, and this can be said as the movement of feminism. FEMINISM In general, feminism is the theory of women’s liberation since the intrinsic in all its approaches is the belief that women suffer injustice because of women’s sex (Humm, 1989: 74). From the inequality that exists between both gender, women want to search equality in the society, they start to speak up their voices in the publicarena. Women themselves must articulate who they are and what role they play in the society. Most importantly, they must reject the patriarchal assumption that women are inferior to men. This started the feminist movement. It was started by the reality that male-female relations is a form of power structure in which men dominate women (Thebaud, 1994: 290). From this starting point the feminist believe that existing inequalities between dominant and marginalized groups can and should be removed. In the practive the feminist scholars attempt to examine beliefs and practices from the viewpoint of the “other”, in this case women, treating them as subjects, not merely objects. Based on all general understanding, it is important to sharpen it into the good shape for not going out of the limitation and wasting buss of explanation of the theory. First of all, it is a long discussion of talking about feminism and its complex sources. To maintain the stability of this research that uses feminism as the knife to slice the discourse of patriarchy reflected in AtiqRahimi’s The Patience Stone, thus the first feminism, the main slicer, continuously will be the main point of theory to discuss. The first wave of feminism appeared in the 19th and early 20th centuries, when women’s suffrage was at the pole position of an industrializing world. In other word, it happened at the age of Victorian age. In 1800, women had little control over their lot in life. The average married female gave birth to seven children. Higher education was off-limits. Wealthier women could use limited authority in the domestic scope but possessed no property rights or economic autonomy. Lower-class women toiled alongside men, but the same social and legal restrictions applied to this stratum of society as well. Somewhat ironically, religion fueled some of the initial social advancements women made at the beginning of the 19th century. The Second Great Awakening, which started in 1790, emphasized emotional experience over dogma, allowing women more leadership opportunities outside of the home. Abolition and temperance movements that shared Protestant undercurrents activated women as well. It is like to what Stuurman, as quoted by Bryson, says that feminist theological arguments were further elaborated in the seventeenth century: for example, some writers used the creation story to argue that Eve was superior to Adam because she wascreated last, or because she was created out of Adam’s rib rather than out of mud and slime (Bryson, 2003: 6). Thus, it can be seen, that in religion, or theologically, the inequality women have, has been rooting to put them down under the knee of men. That means, men are taking higher position in human life where men and women separate them. To talk about the theologically term about the inequality, then women want to get the equality, means that women have something different from the way theology thinks about it and the way of thought is Cartesian with all rationality to think. Bryson notes that the inspiration for these new ways of thinking (feminisms) was the revolution in western philosophy, which had been started in the first half of the seventeenth century by Descartes. According to Cartesian philosophy, all people possess reason, and true knowledge, which is based on experience and self-discovery rather than study of the classics or sacred texts, is in principle available to all. This means that traditional authority is rejected in favor of rational analysis and independent thought, and that customs and institutions which are not in accordance with reason should be rejected. (Bryson, 2003: 6). Therefore, what has been done by feminist is breaking the old thought that is sourced by the empirical way of theology. Moreover, what becomes the main point of this born is the equality that is thought as the right that has been robbed by men and their all system. The first-wave of feminism began in the United Kingdom and the United States around the nineteenth century and lasted until the early twentieth century. The focus of this movement at this time was on de jure inequalities, or officially mandated inequalities. There were many people during this time who were considered to be feminists, Mary Wollstonecraft, Susan B. Anthony, Lucy Stone, Olympia Brown, and Helen Pitts; there are countless more. The first-wave of feminism was monumental to the movement, however, without the continuing second-wave, there would be no hope for feminism in current times, for each wave is connected and dependent on the other's history. In simpler words, feminism is not some simple thing that people can generalize, like it is just an excuse for women to kick men in the balls, and not take care of themselves, or that men and women must be equal at all costs. Feminism is a movement, which has been incredibly important to the success and failures of this country and has been a necessary journey for the women in our country to travel upon so that they can discover and create their own unique place in society. First wave feminists spent hundreds of years in activism, writing, protesting and working for the betterment and equality of their sex and gender. First wave feminists worked not only for suffrage, or the right to vote, but also for the right to an education, the right to work, the right to work safely, the right to the money they earned when they worked, the right to a divorce, the right to their children and the right to themselves and their own bodies. Rights for women can be traced back to the Middle Ages in the Middle East when early reforms under Islam gave women greater rights in marriage, divorce and inheritance. Women in other cultures were not afforded such rights until centuries later. Further improvements of the status of Arab women included things such as the prohibition of female infanticide and recognizing women’s full personhood. The things mentioned above are necessary and were necessary, and in some case, came at the end of long efforts. First wave feminists had to work against this impression, and they had to work against the society that allowed an unmarried woman to be property of her father and a married woman to be property of her husband. The first wave of feminism was the longest, and it is the most taken for granted. It is common now to speak with women who do not identify as feminists who think that feminism is a dirty word, who simultaneously pursue careers and an education, who exercise their right to vote, who own property and benefit from the fruits of their labor. Understanding the history and the efforts of feminism, understanding how much progress they made and how long it took them is important both to those who think they are not feminists, and those who identify as feminists and who live life trying to better the world by the feminist ideal. (Retrieved from uic.edu and pacificu.edu). Victorian feminism is a difficult concept to analyze. On the one hand, some of the greatest reforms of women’s social and legal position before those of the late twentieth century occurred in a few decades of the nineteenth century; on the other, many of those women who were active campaigners—Caroline Norton, Florence Nightingale, Emily Davies, and Barbara Bodichon—were ambivalent about the extent of their own feminism, and over-anxious to distance themselves from unconventional lifestyles and behavior. Moreover, they seemed concerned mainly with the plight of intelligent middle-class single women. Their commitment to respectability gave them something of a timorous or half-hearted allegiance to a more wide-ranging kind of feminism; in any case, their contribution to the feminist cause was often narrowly specialized as they concentrated on a particular campaign—whether for women’s colleges at Cambridge or child custody rights—to the exclusion of others, and many still relied on men to help them with the legal or parliamentary part of their activism. For some, however, it was impossible to avoid being drawn into a wider examination of women’s rights, as happened with Caroline Norton and Harriet Martineau, for example, and by the end of the century, most of the major journals were carrying heated debates about the unsatisfied needs of the modern woman. Beginning initially with spasmodic bursts of activism, first wave feminism gathered pace through the work of specific individuals working for specific ends, until the momentum of events made concern for women’s full participation in social and political life a matter of public interest across the whole political spectrum. This in itself was no mean achievement (Gamble, 2006: 24). According to those all explanations about first wave feminism, that is majorly from west, then it is continued to see this based on the glasses of Islam feminism reflected to AtiqRahimi’sThe Patience Stone. There is a woman that faces a fact of patriarchy system, she cannot do anything except confessing something about the inequality that indirectly getting sympathy for anyone who read to pay the pity about equality of thee Woman should have. The equality is something has been robbed by the patriarchy system, and the way the Woman acts, can be said as feminist movement. As Muslim, this thought can be clearly is seen as east feminist movement. It is like to what Kynsilheto says that it was in this context that some of us reported that Muslim women were subverting the patriarchal Islamist project through what appeared to be a new form of feminism-in-the-making which Muslim women in different parts of the world would soon call Islamic feminism. (Kynsilehto, 2008: 26). Therefore, the understanding of this feminism toward this research goes clearer to see as the relevant theory that will be used to slice the data just to become a good shape of analysis without going out of the limitation. STATUS WOMEN IN AFGHANISTAN The position of women in Afghanistan traditionally has been inferiorto that of men. This position has been continuing to age, socio-culturalnorms, and ethnicity. In fact, Afghan women, even until the beginning of 20thcentury are still being the slaves of their father, husband, father-in-law, and elder brother. Thus, it can be said that the status of women are silence and obedience. The essence of attitude towards women could be clearly seen in the relationshipof the family after the birth of a female baby.The birth of a female baby,particularly in those cases where the mother gives birth to several girls, is the main cause of contracting a second marriage, and it is still happened until nowadays. Girls areusually raised to be good mothers and tolerant housewives. Thus no one pays attention to their education, except in very rare cases in some well-to-do families. Furthermore, they are married to young and even to very old men, in most caseswealthy ones between the ages of 13 and 16, and in certain cases between the ages of 10 and 12, if their parents desire. They were exchanged for what is called “Toyana” or marriage price. Young girls had no right to choose theirfuture husbands, or question their engagement, which is arranged by theirparents. Early marriage is the main cause of suffering for girls in Afghansociety. Such marriages are both physically and psychologically unhealthy,and often resulted in sickness and psycho-neurotic diseases. Many youngmothers pass away during releasing it because of physiological reasons and earlymotherhood.Divorce is an easy act if the husband wants it. Afghan women do not have any right to ask for divorce. The man is the governor, the controller, the dictator, of every authorizing in divorcing. It is a slur for both families.Occasionally, wives were deprived of their rights and claims on their ownchildren. Traditional women refer to their husbands as "Sahib", the lord. Wives aregreatly trusted by their husbands. This great confidence rendered byhusbands has led Afghan wives towards great honesty, chastity, courage, andproper manners. Women are mainly occupied with rearing children, cooking,sewing, milking, weaving, spinning, and other similar house-works. For thosewho can pay for servants, their servants free them from the burden of home duties. Women take part in social occasions and family entertainments,but they separate from men. On all occasions where both sexes take part,they remainsto be separated. According to Scharmann (Kakar, 1971), thedivision of men and women into two separate worlds is pronounced inAfghan society. In entering the world outside their homes, women are toveil themselves. They usually try to hide their faces from men, calling them “Namahram”, though the exception was for women in upper class families,the number of which was very small. Afghan women are patriotic. They love their native land. That is whyAfghan women in time of war helped Afghan warriors in the battle fields byproviding services such as carrying supplies, removing bodies, helpingwounded soldiers, etc. For example, in the second Afghan war with theBritish, Maiden Malalyis known as the symbol of courage at Maiwand war.At present, women take an active part in defending the revolution. They areorganized in committees for such defense. Based on the paraphrasing of Wali M. Rahimi in his book Status of Women: Afghanistan that is supported by UNESCO, therefore it can be accepted that what things happen to the Woman in AtiqRahimi’sThe Patience Stone, is not only a kind of play of the plots of a fiction, but it can be related to the reflection of the reality world, where women are still living in the jail, they live in the armpits of men that are very rotten. HOW AL-QURAN VIEWS PATRIARCHY As a religion that is always involved in patriarchy, Islam actually seems to be like a scapegoat religion. By the showing from the first creature of Adam, the duty of men of being a leader and women should follow their husband, until the greater rights of wealth heritage. Those all constantly strike Islam as a religion that gives privilege to men rather than to women. This all happen, potentially from the miss understanding toward the interpretation of Al Quran.In Al Quran, the holly book of all Muslim, there is told some reason of those wrong perceptions. In a verse from Surah An-NAhl. There is written, Anyone who works righteousness, male or female, while believing, we will surely grant them a happy life in this world, and we will surely pay them their full recompense (on the Day of Judgment) for their righteous works(16:97). This is what is said as the equality of Men and Women. Both men and women are treated with same treatment, and those all based on what they do in the world with regardless what sex they have. Additionally, there are some verses and Surah that show Islam give similar position between men and women, and the difference of the two is not a hierarchal system, but difference of patching each other. This is very different to what patriarchy understands about, therefore, there is no reason to call Islam as patriarchal religion. SILENT VOICE This is a new term that will be a source of question, what does it mean? How can this term raise among all problems that this thesis emerges up? And many questions follow to trace with no end. However, this term is actually taken from the basic problem of the Woman, as the main character, in AtiqRahimi’sThe Patience Stone. The Woman faces problems of patriarchy system, she cannot do anything except following that system. She is just woman, and she has no voice to demonstrate what she feels, but, when her husband comes back in comate condition, she finally can utter everything she feels. Based on this fact, it can be said that the Woman has a chance to say what she feels from the comate condition of her husband, with that moment she says. She voices something, something that is always hidden and repressed. This repressed voice, finally can be seen as the silent voice, because silent literally mean cannot be uttered directly, it exists but it is not heard and listened, even it cannot be heard nor listened. The voice symbolically shows the heart, the feel, and experience. Therefore, it is completely seen as the silent voice of the Woman, definitely. DEPICTION OF PATRIARCHY’S HANDCUFF THROUGH THE WOMAN’S SILENT VOICE IN ATIQ RAHIMI’S THE PATIENCE STONE The things become the crucial issue in Atiq Rahimi’s The Patience Stone is the problem that is faced by the Woman. The Woman here is unnamed character, she has a comate husband after taking back from the war. Here, the Woman delivers everything she has kept, hid, and buried. These feelings are blown up by what she utters to the “dead” husband. Here the conflict emerges as long she delivers it. To start it, the conflict can be rushed to the conflict where the Woman has a sex with her husband at the first night, ‘Oh yes bleeding…I was lying to him, of course.’ She glances keenly at the man, more mischievous than submissive. ‘Just as I’ve lied to you…more than once!’ she pulls her legs up to her chest and wedges her chin between her knees. ‘But there is something I’d better tell you…’ (Rahimi, 2010: 28). There is something different going wrong in this case. On the quotation, the Woman admits to her comate husband that she has been lying to him. What she lies, is the thing happens when they firstly sleep in gathering. Pulling the plot before, the man comes after homing from war. He is as nervous as the woman in facing the first having sex. Then, they finally have a sex. The Husband feels happy because he thinks that the woman is still virgin. The proof is, the blood melts down while the Husband penetrates his penis down. It is accepted because, in oriental countries, culture, women are like the special things. Therefore, the virginity of women is the crucial thing every man should have got. It can be thought carefully when it is compared with western culture. In western culture, a man and a woman can live together although they have not been married, but it is not accepted in mostly eastern culture, moreover in Afghanistan. To get it, men’s culture construct a jail where women are prohibited to be out of house in order to make them saves of being not virgin. However, the blood that melts on the Woman’s vagina is the blood of menstruation. The Husband does not know, and he does not want to know. The way the Husband does it, the way the Husband treats his wife with regardless the condition of the wife appears something. It is a kind of a force, the insisting seems that the Husband, as a man, has a power and right to do everything to the wife. This authority can be belonged to an action of domination of a man to his wife. Further explanation, the way these two creatures marry, is not in a proper equal right. What is meant by this statement is, the Woman marries to her husband in a condition where she has to be sit with a photo because the Husband in on process of war. That is the pity thing for every woman to marry with someone she never sees directly and physically. This marriage happens because the Woman is believed as a woman who has been already of being married. With regardless the love, the feeling, and the desire to marry, the Woman is insisted to marry. This is harsh thing, the hard thing for women to neglect it. Women are poisoned by this system, because if women try to make a move of changing it means that women have not been ruling the law, and it is considered as fighting to God’s rule. As it can be mirrored directly that, this system, this marriage gives something pleasant for the men because they (men) do not have to be so serious in facing the marriage because they can represent their appearance, their existence, in the ceremony. Another fact is, when the Husband has a sex with the Woman, actually the Woman is in the period that means she has menstruation. However, what thing that can stick to every eye is the fact that the Husband firstly meet the Woman, his wife, three years after they marry.‘When you and I went to bed for the first time after three years of marriage, remember! Anyway, that night, I had my period.’ (Rahimi, 2010: 28).From the quotation above, it can be read unmistakably that the Woman meets her husband firstly after three years passed. This is added the explanation above that the Woman is jailed in the system of patriarchy. The Woman cannot break the rule, she has to follow the rule, she has to be laid down on the feet of a man. It can be imagined, how can a marriage is not attended by one of the couple? It is really strange and seemed not to be a fair marriage. Additionally, the Woman marries to her husband is caused by the time she has to marry. Moreover, her sister has been sold to a man because her father cannot pay the debt after being lost in his bet. After having a sex, the days after, the Husband should go to the war again. It means that he has to leave his wife again. The Woman, as a woman generally in the world, must feel sad of being left by the husband. Therefore, the Husband looks to be a pride thing for everyone in Afghanistan, because he struggles for nation, for religion, for Afghanistan. Although, what the Husband does is sacrificing the happiness of the Woman. This is the voice of the Woman in front of the comate Husband. She utters everything she feels, what she utters means that she has been keeping, holding, and defending her emotion and anger because of the relation with her husband. She marries with a man, and during the marriage, for ten years, she never speaks, she never does something husband-wife does generally such a chit-chatting, joking, giving romantically action, and other actions. The coming of the Husband is only run out by drinking, partying, and laughing with all his friend, then he wants to have sex with his husband, the Woman. Therefore, it means that the woman is only an object of sexuality, object to deliver the Husband desire of sexuality, the object that is only for satisfying his ambition of the desire. Within this context, within this culture that asks every woman to fulfill the desire of the husband, becomes the thing that can be good and bad. Generally, it is good for a normal relation that has good husband and wife. For example, the filling what husband desires can strengthen the relation of the two, between the husband and the wife. However, the context that the Woman faces is different. She is very seldom of meeting with his husband, she never speaks, talks, and make conversations. Then the Husband comes home, and wants to have sex after drinking and partying. Can it be looked as a duty for every woman in the world to fill what the husband wants? This is unfair thing. This is the thing that can slice the feel of every woman. Women are also creature, they are human being, they also have feeling and desire. They want to be felt, they want to treated humanely. If the Husband just want to throw out his desire and after that he goes off again. It makes the impression of the Woman that she just a whore of the man, she is just a slut of the Husband, she is only a harlot of his husband. This s irony, but this is what happens to the Woman in Atiq Rahimi’s The Patience Stone. Because the setting is in Afghanistan, it can be reflected that something happens to the Woman, is what the things happen to some women in Afghanistan. Talking about Afghanistan, it must relate to the system they use. Afghanistan is a complicated country. Therefore, what can be inferred from the explanation has been noted in the understanding before about the position women in Afghanistan, is the women have no freedom to move, to express something, to say something such as “Excuse me, I want to divorce you.” Or something like “Um… Sorry we need to discuss it before.” The fate of women seems to have been robbed out. They do not have anything in the world, everything they want to say, everything they want to deliver based on what they feel, based on what they think is unfair, is unsaid, and it is kept in heart. What else that has to be said that this system is called as patriarchy system. Indeed, it is Islam, but it is longer used as what equality in Islam has been written on the holy Koran. This is caused by the wrong interpretation of human, the wrong interpretations are finally used as the culture, and for the God’s sake, it is inherited. The Quran makes it clear that Women and Men are equal in the eyes of God. This is the weakness of human, to see something they always see it by what they can accept, although God has different point of view. One of the most misunderstood areas in Islam is the position, the situation, and the condition of women in the religion. The universal view in the West is that Muslim women are subjugated and almost seen as property or the object of men. Although, not all Muslims deal with that statement that women as inferior, this is unfortunately true in some segments of the Muslim world and this treatment is supposedly reasonable thing by the religion. However, when it is looked at the basis of the religion, the Quran, it can be seen a different picture. In the Quran God makes it very clear that men and women are equal. Their Lord responded to them: "I never fail to reward any worker among you for any work you do, be you male or female - you are equal to one another. Thus, those who immigrate, and get evicted from their homes, and are persecuted because of Me, and fight and get killed, I will surely remit their sins and admit them into gardens with flowing streams." Such is the reward from GOD. GOD possesses the ultimate reward. (3: 195). The only criterion for distinguishing among the people. Based on what those show, it can be articulated that God seems to have no distinguishing, or special thing to differ between men and women. The two can have sins, the two can hbe living in the paradise, the promised place. If the God seems to say that, why men creates their own understanding to control women in their armpits, is that a kind of breaking the rule of God whereas God say that there is no difference between men and women, the two can live in paradise and have sins. If the paradise is for good human, and men try to be good by slaving women, and women try to be good women by being slaved by men, is that a kind of justice? Men can live freely by slaving women in the world, and slaving is kind of joyful action. They do not have to be pregnant, they do not have to be working at house, wiping the shits of the baby, feeding the baby, menstruation, and busy of massaging their husband. If they (women) have to do so as their duty, they should have the same result of what they have done, the same right of not being slaved. They should have similarity, because of what they do for men are rightfully consisted of rights. However, men, the culture of men, the system of men, the wrong interpretation, makes them fall to the disgusting thinking about women. How can that clear verses be ignored? Why are women treated so poorly in some Muslim communities? The answer lies in the fact that those communities take other sources besides the Quran as the basis of their religion. There are many Hadiths that degrade women. In addition, the pre-Islamic cultures of much of the Muslim world do not value women and have little use for them. The following verses demonstrate this fact: Long and complicated, the tradition that brings and leads the system of men to mostly Muslim nations, here is Afghanistan. However, it can be traced that what makes this becomes the intimate problems of Afghanistan is their condition. Their variety of religion and the territorial that is surrounded by West and East culture makes them are easy to be got down, especially in their rule. Islam, where the verses are delivered beautifully, but it is interpreted wrongly, and makes the wrong system of men. There are difference between men and women, but the difference does not mean they are not equal. They have same duty and right, the same means to the effect rather than the direct meaning of duty, so does the right. However, this right does not longer exist for many women, and it can be represented by the Woman in AtiqRahimi. Again, she has to admit that to be married with the Husband is not what she wants. ’Your mother, with her enormous bust, coming to our place to ask for the hand of my younger sister. It wasn’t her turn to get married. It was my turn. So your mother simply said, “no problem, we’ll take her instead!”, pointing her fleshy finger at me as I poured the tea. I panicked and knocked the pot over.’ She hides her face in her hands.in shame, or to dispel the image of a mocking mother in law. ‘as for you, you didn’t even know this was happening. My father, who wanted nothing more, accepted without the slightest hesitation. He didn’t give a damn that you weren’t around! Who were you, really? No one knew. To all of us, you were just a title: the hero! And, like every hero, far away. Engagement to a hero was a lovely thing, for a seventeen year old girl. I said to myself. (Rahimi, 2010: 53—54). Here is told that the Woman does not have any right to choose which man she wants to be married to, because her mother selects the man for her. It shows that the power of parents is strongly grabbing the children, and the children that gets the bigger grab is woman. Women are considered as slow, weak, and brittle. Thus, it is not right if women are given a chance to choose men. Furthermore, the Women does not love the man she marries. It is a kind of insisting. Why should be woman? This is the patriarchy system, the system that control women. The more ironical thing happens to the Woman in Atiq Rahimi’s The Patience Stone is, she marries with a man she never knows, and even in the marriage ceremony, she marries to a photo. ‘… they celebrated our engagement without the fiancé. Your mother said. “don’t worry, victory is coming! It will soon be the end of the war, we will be free and my son will return!” Nearly a year later, your mother came back. Victory was still a long way off. “It’s dangerous to leave a young, engagement woman with her parents for such a long time!” she said. And so I had to be married, despite your absence. At the ceremony, you were present in the form of photo and that wretched khanjar, which they put next to me in place of you. (Rahimi, 2010: 54). Based on the quotation above, it can be read obviously that the Woman marries to a man she never knows and during the marriage ceremony, she just sits next to a photo, not the man she marries to. This is an irony fact, the Woman must feel sad, besides the force of marrying the man she never knows, she must also feel sad of this moment. This is an unfair thing for woman, and can it be said that this is the fair thing for woman to marry with a photo? Furthermore, for years the Woman is not allowed to jostle, to join with a group, with neighbors, and friends. She has to be in home, doing everything in home. The home is like the jail of her, she is prohibited of talking to anyone. And I had to wait another three years. Three years! For three years I wasn’t allowed to see my friends, or my family…it was not considered proper for a young married virgin to spend time with other married women. Such rubbish1 I had to sleep in the same room as your mother, who kept watch over me, or rather my chastity. And it all seemed so normal, so natural to everyone. To me, too! I didn’t even know how lonely I was.’ (Rahimi, 2010: 54). The way her mother in law treats her can be analogized that the Woman seems like a prisoner. She is forbidden to interact with the other side of the house, she has to sleep with her mother in law while the Husband is in war. The mother always keeps watching on her, and it is like a guard in the jail, and the woman is the prisoner. She is like a creature who is born to be kept watching, with no right to do, every move she makes is something her mother in law catches.When she is like a prisoner, she must be the fault one whether she is fine or doing a mistake. It is portrayed to this below quotation. Those all are what the Woman feels and it is portrayed in a conclusion where patriarchy system in Atiq Rahimi’s The Patience Stone is drawn. The Woman is the representation of this portrayal, she feels in jail, she feels like a prisoner, no right and no freedom to move. She marries to a man she never knows, her sister becomes the stake of her father’s bet, and she forced to be pregnant although the Husband is the unfertile one. She is insisted to meet someone like a priest to consult the pregnant, and the priest is actually a procurer. She is asked to get in a room, and a man with blindfolded penetrates her until she gets pregnant. The way her mother insists her to get pregnant with not knowing the condition of her son, makes the Woman has a baby from a man she does not know. This the cruel of the patriarchy, when women do not have any right to speak something, they are jailed, and the only one thing the Woman in the story can do is, delivering everything she feels to her comate husband. With a silent voice, she utters and posits herself. THE IMPACT OF THE WOMAN’S SILENT VOICE IN ATIQ RAHIMI’S THE PATIENCE STONE As the response of facing this problem, the Woman cannot do anything except telling the truth of what she feels, what she hides, what she wants to deliver, because she does not want to hurt anyone. Therefore, she wants to tell it to no one, besides that she must be afraid of telling what she feels because what she faces is the culture, the misunderstood religion, and social truth. This problem is delivered through this below quotation, she thinks that it is better to keep silent and to tell to no one. ‘I never wanted anyone to know that. Never! Not even my sisters!’ she leaves the room, upset. Her fears echo down the passage. ‘He’s driving me mad. Sapping my strength.Forcing me to speak.To confess my sins, my mistakes.He’s listening to me. Hearing me.I’m sure of it. He wants to get to me…to destroy me!’ (Rahimi, 2010: 60—61). This is what happens to the Woman’s sister. Her sister is forced to marry, her father sells her sister because her father defeats in bet. However, what can the Woman do? She is just a woman, she has no voice, her voice is not to be heard or listened, she is just a creature that is created by not deliberation, therefore, woman should be in room, cooking, bearing baby, feeding baby, and doing “female” activity. She does not have to have something like man, like voicing voice. This shows that the Woman posits herself in a mute, in silence, and in the broken heart with no fight back. The culture has constructed them t be like this, silence and mute. This is the best position the Woman can replace because if she wants to break the rule, she must be destroyed, tortured, and punished by the law the men create. One of the best way, besides keeping silence, is telling the truth to God. When her husband is comate, the Woman always prays on her Husband. Her Husband is just comate, cannot respond, cannot do anything. A hand, a woman hand, is resting on his chest, rising and falling in time with his breath. The woman is seated. Knees pulled into her chest. Head sunk between her knees. In the other hand, the left, she holds a long string of black prayer beads. She moves them between her fingers, telling them. Silently.Slowly.In time with her shoulders. In time with the man’s breath. Within reach, open at the flyleaf and placed on a velvet pillow, is a book, the Koran. Her plump, dry, pale lips are softly and slowly repeating the same word of prayer. (Rahimi, 2010: 2—3). This is what the Woman does, he prays for the Husband, although everyday it seems no worth, no use, and it even seems to be in vain. However, as a Good wife, she always prays, and never quits for stopping praying. This is the way the Woman posits herself, although she gets unfair life, although her life is grabbed by the system of men, although her happiness is robbed by the injustice, she just tries and keeps trying to be a good wife fro her evil Husband. The way the Husband keeps silence and receives all things the Woman tells, is analogized as the Patience Stone. It is the mythical stone for Muslim in Hajj, the stone that is very soft and can release all burden. Probably, this is why the Woman tells it to her comate Husband. There are so many internal conflicts the Woman faces, and she almost has a plan to leave her comate Husband. However, she is a god wife, and she is so sorry of having it. It is reflected on this below quotation. ’Forgive me’, as she strokes his arm. ‘I’m tired. At breaking point. Don’t abandon me, you’re all I have left.’ She raises her voice : ‘Without you, I have nothing. Think your daughters! What will I do with them? They’re so young…’ She stops stroking him. ‘The Mullah won’t come today,’ she says with some relief (Rahimi, 2010: 14—15). In this quotation, it shown and portrayed that the Woman is almost surrendered, she almost quits, she is almost getting tiring. Her frustration is caused by the condition of the Husband that is not different days by days. However, she remembers about her daughter, and it adds something in her heart not to leave the Husband. Based on this fact it can be seen that the Woman is trying to posit herself in a god way, she is just trying to be a good wife, a good Muslim who works the rule of not leaving the Husband and doing everything for the Husband, although the Husband is in comate condition. This portrayal, is the form of faith, the Woman is really special woman, by the condition that can strike her, the situation that can make her angry, the experience that can make her has a revenge for the injustice, she keeps having a feeling to take care of her Husband. Then, the reflection of the Woman to posit herself is clearly seen b this quotation. As a good mother, the Woman also treats her children with lovely treatments. It is shown by this quotation below that shows that the children are not allowed to disturb the comate father. ‘Don’t be frightened, darling. I’m here.’ The mother reassures her : ‘I wasn’t shouting. I was talking to your father.’ They walk away from the door. ‘Why are you calling my father Al-Qahhar? Is he cross?’ ‘No, but he will be if we disturb him.’ The little girl falls silent (Rahimi, 2010: 17). The way the Woman asks to her children not to disturb their father who is comate shows that the Woman keeps the Husband, she does not want her Husband gets worse by the disturbing. This is showing the Woman posits herself in treating her Husband. Based on the experience when she has to marry with a photo, the experience where she has to be penetrated while she has menstruation, until her Husband’s brothers who always spy the Woman while she takes a bath, she does not have any revenge. If she has, she must kill the Husband easily because the Husband is between the condition of dead and alive. He is comate, and it is very easy for everybody to kill him, no exce